2010
DOI: 10.1177/1352458510366857
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose naltrexone on quality of life of patients with multiple sclerosis: a randomized placebo-controlled trial

Abstract: The study clearly illustrates that LDN is a relatively safe therapeutic option in RRMS and SPMS but its efficacy is under question and probably a long duration trial is needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 28 publications
(33 reference statements)
0
59
0
1
Order By: Relevance
“…Clinical trials using OGF or LDN as therapy have reported improved quality of life in MS patients (Cree et al, 2010;Sharafaddinzadeh et al, 2010), and together, the data warrant further randomized, controlled clinical trials in order to gain approval of OGF and/or LDN as treatment for patients with relapse-remitting or progressive MS.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical trials using OGF or LDN as therapy have reported improved quality of life in MS patients (Cree et al, 2010;Sharafaddinzadeh et al, 2010), and together, the data warrant further randomized, controlled clinical trials in order to gain approval of OGF and/or LDN as treatment for patients with relapse-remitting or progressive MS.…”
Section: Discussionmentioning
confidence: 96%
“…Information on the length of confirmed MS, as well as the length of time on either Copaxone or LDN, was provided by the patient, and not documented by medical records. 5 ]-enkephalin and b-endorphin concentrations Human serum samples were analyzed using five ELISA kits for [Met 5 ]-enkephalin and one human b-endorphin kit. Serum [Met 5 ]-enkephalin levels for all MS and non-MS patients are presented in Figure 1(a).…”
Section: Ms Patient Demographicsmentioning
confidence: 99%
“…However, the financial burden of individual therapy can range upward to $60K annually (37), and side effects still reduce compliance and thereby overall efficacy (38). Randomized clinical trials of enkephalins or LDN are limited (40)(41)(42)(43), possibly because use of LDN has been reported to have a few side effects, and large pharmaceutical companies are not interested in sponsoring studies on a repurposed drug (i.e., LDN) that is already FDA approved at substantially higher dosages. Nonetheless, there remains a need for safe, effective treatments that are alternatives to the β-interferon products.…”
Section: Clinical Studiesmentioning
confidence: 99%